2017
DOI: 10.1038/srep45846
|View full text |Cite
|
Sign up to set email alerts
|

International incidence and mortality trends of liver cancer: a global profile

Abstract: We examined the global incidence and mortality rates of liver cancer, and evaluated the association between incidence/mortality and socioeconomic development (Human Development Index [HDI] and Gross Domestic Product [GDP]) using linear regression analysis. The average annual percent change (AAPC) of the trends was evaluated from join-point regression analysis. The global incidence of liver cancer varied widely by nine-fold, and was negatively correlated with HDI (men: r = −0.232, p = 0.003; women: r = −0.369, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
186
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(198 citation statements)
references
References 29 publications
5
186
0
7
Order By: Relevance
“…22 In 2012, Eastern Asia was noted to have the highest HCC-related incidence and mortality in both genders in the World. 23 According to Asian-Pacific clinical practice guideline, there was a clear difference of incidence and mortality in this region. 22 For example, the cause of HCC in Japan (mainly HCV) differs greatly from other countries (mainly HBC) in the region.…”
Section: Discussionmentioning
confidence: 99%
“…22 In 2012, Eastern Asia was noted to have the highest HCC-related incidence and mortality in both genders in the World. 23 According to Asian-Pacific clinical practice guideline, there was a clear difference of incidence and mortality in this region. 22 For example, the cause of HCC in Japan (mainly HCV) differs greatly from other countries (mainly HBC) in the region.…”
Section: Discussionmentioning
confidence: 99%
“…As for breast cancer, wealthier countries tended to have higher incidence rate (14,15), with the ASIR in more developed countries two times as high as in less developed countries (10). In China, positive correlation between breast cancer mortality rate and GDPPC was found (16). Researches based on GLOBOCAN data showed that liver cancer incidence and mortality was negatively correlated with GDPPC (17), and cervical cancer incidence and mortality rates in developing countries were two-fold and three-fold higher respectively than women in developed countries (18).…”
Section: Introductionmentioning
confidence: 92%
“…With regard to China, there are only a handful of articles on the association between economic factors and the pattern of a certain cancer in certain cities (16,22). High-GDPPC areas had both the highest crude incidence and mortality rates, followed by middle-and low-GDPPC areas.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, age‐adjusted mortality rates for liver cancer increased by 43% between 2000 and 2016 . Increasing secular trends in incidence and mortality have been observed across many countries including the United Kingdom, Poland, Brazil, Germany and Norway . Major risk factors for liver cancer include hepatitis C virus (HCV) infection, hepatitis B virus (HBV) infection, heavy alcohol drinking and nonalcoholic fatty liver disease (NAFLD) .…”
Section: Introductionmentioning
confidence: 99%